Comparison of Kirchhoff Migration and Reverse Time Migration in the Time Domain: Case Study of Field "Y" North West Java Basin - Moefti, Omar; Haris, Abdul (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2023)
This study evaluates and compares two seismic migration methods, namely Kirchhoff Migration and Reverse Time Migration (RTM), using 2D seismic data in the North West Java Basin. The main objective of the research is to investigate the relative performance of the two methods in restoring the position of reflectors that have undergone distortion due to the propagation phenomenon of seismic waves. The study involves a detailed analysis and comparison of these methods in terms of accuracy and computational time efficiency. The results show that the Kirchhoff Migration method achieves high accuracy in handling reflectors with significant dip angles. Additionally, this method also demonstrates good computational time efficiency. On the other hand, Reverse Time Migration, although recognized as a sophisticated approach, shows less satisfactory results under the conditions of this study, highlighting its dependence on data complexity and velocity model optimality. This research provides important insights for the appropriate selection of migration methods based on geological characteristics and existing seismic data. Kirchhoff Migration emerges as a superior choice, especially for regions with geological complexity and high dip angles. In conclusion, the selection of migration methods should carefully consider the specific characteristics of the relevant region to achieve optimal results.